The influence of soil carbonates on highbush blueberry plants in the conditions of the Kabardino-Balkarian Republic - E. M. Egorova; F. D. Taumurzaeva; A. A. Abregov (Новые технологии, 2024)
The article studies the influence of soil carbonates on the plants, the yield and the quality of highbush blueberries in the conditions of the Kabardino-Balkarian Republic. The carbonates in the soil solution lead to an increase in soil pH, which negatively affects its development. High bush blueberries have special soil requirements for normal growth and development. It is necessary to provide the plant with a breathable substrate with an optimal acidity level of up to 5.5 units. Acidic conditions are necessary due to the unique structure of the root system: highbush blueberries are completely devoid of root hairs; their function is performed by a colony of fungi, which constitutes mycorrhiza in symbiosis with the plant. Mycorrhiza functions only in acidic conditions. The research provides average data for the period of 2021-2023. Blueberry plants grown in carbonate areas are characterized by weak growth, few shoots to form, low foliage and chlorosis due to reduced food availability. The size of the berries and their taste play a huge role for producers. The measurement of this parameter showed that in the main part of the field, under the best growing conditions, the average diameter of the berries is 17 mm, which is 23.5% more than in carbonate areas, where the diameter is, on average, 13 mm. The accumulation of sugar in berries with increased soil carbonate decreases by2.3%, which significantly affects their taste. As a result of the research, a negative effect of soil carbonates on the development of blueberry plants has been noted, as well as yield reduction by 79.5%. The negative effect of increasing pH to neutral or, especially, slightly alkaline on plant development is associated with deterioration of nutrition and poor development of the root system.